Situationsgerechtes kirchliches Handeln in der Spätantike und heute am Beispiel des Johannes Chrysostomos - Ritter, Adolf Martin (Kerygma und Dogma, 2009)
With the intention of honouring Fairy von Lilienfeld (Erlangen), the oustanding expert in the field of Russian Orthodox Theology and Spirituality as well as Orthodox-Lutheran Dialogue, on the occasion of her ninetieth birthday, the paper starts (in a first section, titled »Preliminary clarifications«) with reflecting two items: a) how it can be understood that the organizers invited just a {!patristic} scholar to honour F. von Lilienfeld; b) how it can be explained that this scholar, a Lutheran theologian, is willing to speak of the »{!holy} John Chrysostom«, although it seems to be agreed that protestants don't have and accept {!sancti} (which is, in the eyes of the speaker, a - widely held - error [cf. {!Confessio Augustana} XXI]). In a second, very short section (titled »Chrysostom vis à vis the challenges of his time«) follow brief outlines referring to his biography and literary heritage, whereas the third and last section offers a more detailed discussion of the problem: »If and what we (i.e. modern Lutherans) could learn from Chrysostom?«, and this especially concerning an up-to-date way of acting, in conformance with the actual situation, by members as well as functionaries of the church. On the understanding that what matters today is not to interpret protestantism mainly in contrast to catholicism (as A. von Harnack commended) but to ask {!together} what the Christian faith might actually mean and require as its consequences, the speaker is convinced that there is a lot we could learn from Chrysostom, although, no doubt, the circumstances meanwhile have fundamentally changed, compared with the time of the church father.